Pengaruh Return On Asset (ROA), Price Earning Rasio (PER), Earning Per Share (EPS), Debt to Equity Rasio (DER), Price to Book Value (PBV) Terhadap Harga Saham (Study Kasus Pada Perusahaan Media Pertevisian dan Media Masa Yang Terdaftar Di Bursa Efek Indonesia - Putri Rahayua; Enny Arita (CV. ITTC INDONESIA, 2024)
The capital market is a means for companies to sell shares in an effort to increase long-term funding needs. With the implementation of new government regulations regarding the closure of analog television broadcasts, the selling value of shares in compact television media companies has decreased. This research examines Return On Assets (ROA), Price Earning Ratio (PER), Earning Per Share (EPS), Debt to Equity Ratio (DER), and Price to Book Value (PBV) which are financial ratios to determine the performance of a company. company. company. This research aims to determine the effect of these five financial ratios on share prices in television media companies listed on the Indonesia Stock Exchange in 2018-2022. With a sample of 4 companies. The results of this research partially (ROA) and (PER) have an effect on stock prices, while (EPS), (DER), and (PBV) have no effect on stock prices.